Specifying the information effect: reference points and procedural justifications affect legal attitudes in four survey experiments - Grimmelikhuijsen, Stephan (Journal of experimental criminology, 2021)
Objectives Providing detailed information about sentencing reduces punitive attitudes of laymen (the information effect). We assess whether this extends to modest information treatments and probe which specific informational types matter most. In addition to previous studies, we include affective measures and trust in judges. Methods In four survey experiments, 1778 Dutch participants were exposed to a sentence concerning a serious traffic offense resulting in a fatal accident. Studies 1 and 2 explore the effect of a press release on negative and positive affect. Studies 3 and 4 explore the effects of various types of information on affect and trust in judges. Results Modest information treatments generally heightened positive affect, reduced negative affect and—sometimes—increased trust in judges. Providing procedural cues and reference points about the sentence had a sizable effect on legal attitudes. Conclusions The information effects pertain to a broader set of attitudes than currently presumed in the literature. Furthermore, subtle treatments containing procedural cues and reference points can change attitudes towards judicial verdicts. Future research needs to explore if this finding extends to other contexts.